The role of antioxidants in restoring MAPK 14 and a DNA damage marker level following autophagy suppression. Issue 12 (9th December 2020) - Elbialy, Abdalla
Abstract : Abstract : Autophagy is a lysosomal degradation mechanism for elimination and recycling of damaged intracellular organelles and proteins. Recent studies have shown that autophagy could help reduce oxidative stress by removing oxidized proteins and damaged mitochondria. Autophagy deficiency is associated with the disruption of many intracellular biological processes. Using bioinformatics tools and fibroblast immunostaining technology, I tried to investigate whether oxidative stress is involved in mediating the effect of autophagy suppression on certain cell biological processes and signalling pathways. Many pharmaceutical components have different modes of action to suppress autophagy. In this study, I performed analysis on autophagy suppression induced by neutralizing lysosomal pH (NH4 Cl and bafilomycin A1). Bioinformatics analysis of GEO data, GSE60570 accession number, revealed that p38 signalling induction and DNA damage response are among the main disrupted signalling pathways in bafilomycin A1-treated RPE-1 cells. Likewise, fibroblast immunostaining showed that autophagy deficiency established by ammonium chloride (NH4 Cl) has significantly increased P38 signalling, DNA damage marker (H2A.X), and oxidative stress marker (dityrosine). I therefore investigated the role of oxidative stress and whether antioxidants treatment could reverse autophagy suppression effects on p38 signalling and DNA damage response. Importantly, antioxidant treatment clearly restored P38 signalling and H2A.X levels in autophagy-suppressed fibroblast cells. Indicating that oxidative stress might be associated with the harmful effect of autophagy suppression.